KREDIBILITAS PEMBERITAAN MEDIA BATAM POS TERHADAP PERSEPSI COVID-19 MASYARAKAT KOTA BATAM - Juniati, Yosiana; Rorong, Michael Jibrael (SCIENTIA JOURNAL, 2021)
The purpose of this study is to determine the influence of the credibility of the Batam Pos media covarage on the perception of Covid-19 of the Batam city. Media coverage over the past few years has been filled with news related to Covid-19 or the corona virus. This deadly virus is so interesting to discuss and has given a different perception among the public. The research method used is a quantitative method with the type of survey research. Based on the results obtained from data processing, there is an influence of Batam Pos media credibility on the perception of Covid-19 of the people of Batam city based on t-test analysis, this presents table t count > t table 7.073 > 0.155, which means there is a significant effect at a significant level of 10%. The influence of the credibility of the Batam Pos media on the perception of Covid-19 of the people of the city of Batam is evidenced by the results of the 33.8% analysis of the impact of Batam Pos media credibility.